Monoclonal antibodies to rat leukocyte surface antigens, MHC antigens, and immunoglobulins. - Puklavec, M; Barclay, N (2001)
The CD nomenclature used for human-leukocyte surface antigens is now being widely applied to naming their homologs in other species. This appendix catalogs those CD antigens that have been clearly defined in the rat. There are also many other antigens defined in the rat, but only those for which good biochemical data are available, such as amino acid sequences, are given here. The most commonly used antibodies are summarized.